2022
DOI: 10.23869/bphjbr.27.2.20228
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimension Glyceraldehyde-3-Phosphate Dehydrogenase protein structure of substitution and insertion sequences of GAPDH gene of chicken drumstick meat (Gallus gallus)

Abstract: The study aimed to observed the 3-D structure of GAPDH protein and identify the GAPDH gene sequences mutation of chicken drumstick meat (Gallus gallus). The sample of chicken meat was randomly taken in four districts in Malang city. In this study, the DNA was isolated from drumstick meat chicken samples, amplified using proper primers, and then sequenced using ABI 3730xl DNA Sequencer. The DNA sequences alignments analyzed by BioEdit software and the control sequence of GAPDH gene was obtained from NCBI GenBan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The NFAT activation can induce a muscle fiber type switch toward a slow-twitch and oxidative phenotype, related to the increased expression of a subset of genes associated with type I myofibers such as myoglobin and troponin I slow [ 18 , 19 ]. We have previously reported that the substitution mutation of GAPDH gene sequences of chicken broilers can change amino acid sequences and the three-dimension structure of GAPDH protein [ 20 ]. Myoz family proteins are often used in the field of animal husbandry.…”
Section: Discussionmentioning
confidence: 99%
“…The NFAT activation can induce a muscle fiber type switch toward a slow-twitch and oxidative phenotype, related to the increased expression of a subset of genes associated with type I myofibers such as myoglobin and troponin I slow [ 18 , 19 ]. We have previously reported that the substitution mutation of GAPDH gene sequences of chicken broilers can change amino acid sequences and the three-dimension structure of GAPDH protein [ 20 ]. Myoz family proteins are often used in the field of animal husbandry.…”
Section: Discussionmentioning
confidence: 99%